2013
DOI: 10.4103/2277-9167.118121
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing shunt malfunction in patients with tuberculous meningitis

Abstract: Hydrocephalus secondary to tuberculous meningitis (TBM) is a challenging condition to treat. Though ventriculo-peritoneal (VP) shunt is an accepted modality of treatment for hydrocephalus in TBM, there is a high rate of complications associated with the same. The study was planned to evaluate various factors associated with shunt malfunction in patients undergoing VP shunt surgery for hydrocephalus due to TBM. A retrospective review of all the patients undergoing VP shunt and shunt revision for TBM b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…It predisposes to develop a shunt block leading to shunt revision. 33 Based on Jamjoom et al, 34 catheters left in situ for over 8 days had a higher risk of EVD-related infection (ERI) compared with those removed at 7 days or less (odds ratio = 2.54 [95% confidence interval: 1.14–5.7]; p = 0.02). The other studies also have proven that prolonged catheterization duration plays an essential role in ERI.…”
Section: Discussionmentioning
confidence: 99%
“…It predisposes to develop a shunt block leading to shunt revision. 33 Based on Jamjoom et al, 34 catheters left in situ for over 8 days had a higher risk of EVD-related infection (ERI) compared with those removed at 7 days or less (odds ratio = 2.54 [95% confidence interval: 1.14–5.7]; p = 0.02). The other studies also have proven that prolonged catheterization duration plays an essential role in ERI.…”
Section: Discussionmentioning
confidence: 99%
“…26 But to recommend the routine use navigation system for the insertion shunt, we need a multicentric study with large sample size. Ambekar et al 27 and Kamat et al 28 showed in their study that patients with increased protein levels in CSF are at a high risk of VP shunt blockage. In our study, we found more complications in the patients with elevated CSF protein of more than 40 mg per deciliter.…”
Section: Discussionmentioning
confidence: 95%
“…Ambekar et al 27 and Kamat et al 28 showed in their study that patients with increased protein levels in CSF are at a high risk of VP shunt blockage. In our study, we found more complications in the patients with elevated CSF protein of more than 40 mg per deciliter.…”
Section: Discussionmentioning
confidence: 95%
“…We also found that CSF cell count, protein and sugar levels did not have a signicant effect over revision of shunt as reported in other studies. [6] Ambekar et al [20] suggested patients with pre-operative hyponatremia and high CSF protein concentration have a higher incidence of shunt malfunction. In our study mean value of ventricular size (FH/ ID ratio) was reduced from 60.89% to 43.7% and this reduction in ventricular size was statistically signicant.…”
Section: Discussionmentioning
confidence: 99%